2004
DOI: 10.1111/j.1537-2995.2004.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐extremity deep venous thrombosis complicating whole‐blood donation

Abstract: Although serious complications from whole-blood donation are rare, they may occur. Deep venous thrombosis should be considered in a donor presenting with increasing pain and swelling after blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Today, hemolysis and air embolism are rarely seen with modern blood collection equipment [9]. Severe outcomes [30,43], arterial puncture [44], citrate toxicity, severe injuries to subcutaneous nerves [45,46,47,48,49,50], thrombosis of upper extremity veins [51,52], formation of an arteriovenous fistula [53,54], pseudoaneurysm [55,56,57], or compartment syndrome [58] are all extremely rare, as are some other rare events [59]. We did not see any of these rare UEs [60,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Today, hemolysis and air embolism are rarely seen with modern blood collection equipment [9]. Severe outcomes [30,43], arterial puncture [44], citrate toxicity, severe injuries to subcutaneous nerves [45,46,47,48,49,50], thrombosis of upper extremity veins [51,52], formation of an arteriovenous fistula [53,54], pseudoaneurysm [55,56,57], or compartment syndrome [58] are all extremely rare, as are some other rare events [59]. We did not see any of these rare UEs [60,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…There are two reported cases in the English medical literature. [1][2][3] Our institution had three UEDVT cases after whole blood donation within a 13-month period. We report the three cases and also review the two cases reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Upper‐extremity deep venous thrombosis (UEDVT) after whole blood donation is rarely reported. There are two reported cases in the English medical literature . Our institution had three UEDVT cases after whole blood donation within a 13‐month period.…”
mentioning
confidence: 99%
“…To date, 27 cases have been reported in the English-language literature, including those reported only in abstracts, of which 2 cases involved apheresis (22,23), 4 involved whole-blood donation (24,25), and the others did not mention the method of donation (26,27). Table 3 describes the 8 cases for which the details were recorded.…”
Section: Discussionmentioning
confidence: 99%